2023
DOI: 10.1149/1945-7111/ace383
|View full text |Cite
|
Sign up to set email alerts
|

A Raman Study on the Speciation of Different Metal Ions in an AlCl3–Based Ionic Liquid

Abstract: The speciation of Cr, Zn, and Sn in AlCl3/1-ethyl-3-methylimidazolium chloride containing CrCl2, ZnCl2, and SnCl2, respectively, has been studied by cyclic voltammetry (CV), Raman spectroscopy and density functional theory (DFT) calculations. Addition of the respective metal salt causes the current waves in the CV to decrease, indicating a reaction of the metal salts with Al2Cl7 -. Compared to the neat electrolyte, the Raman peaks of Al2Cl7 - decrease while the AlCl4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Notably, the shift of the 27 Al signals to lower frequencies indicate fewer Al 2 Cl 7 – species are present when the urea/[EMIm]Cl ratio increases, which is a crucial species for the electrodeposition of aluminum metal. 27 Al NMR spectra acquired by Malik et al at −10 °C in AlCl 3 –urea binary mixtures showed significant changes in aluminum speciation with changing AlCl 3 /urea molar ratios. The variation in electrolyte speciation could result in a different and/or multiple electrodeposition pathway(s), as Al-urea complexes such as [AlCl 2 (urea) 2 ] + have also been proposed to enable Al electrodeposition in addition to chloroaluminate Al 2 Cl 7 – anions. , Gordon et al used thermochemical calculations to show that while these Al-complexed species can participate in Al electrodeposition reactions in AlCl 3 –urea mixtures, electrodeposition of Al metal by the Al 2 Cl 7 – species , is more favorable based on Gibbs free energy. Increasing the urea concentration resulted in a clear increase in the broad peak at 74 ppm, attributed to the [AlCl 2 (urea) 2 ] + complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the shift of the 27 Al signals to lower frequencies indicate fewer Al 2 Cl 7 – species are present when the urea/[EMIm]Cl ratio increases, which is a crucial species for the electrodeposition of aluminum metal. 27 Al NMR spectra acquired by Malik et al at −10 °C in AlCl 3 –urea binary mixtures showed significant changes in aluminum speciation with changing AlCl 3 /urea molar ratios. The variation in electrolyte speciation could result in a different and/or multiple electrodeposition pathway(s), as Al-urea complexes such as [AlCl 2 (urea) 2 ] + have also been proposed to enable Al electrodeposition in addition to chloroaluminate Al 2 Cl 7 – anions. , Gordon et al used thermochemical calculations to show that while these Al-complexed species can participate in Al electrodeposition reactions in AlCl 3 –urea mixtures, electrodeposition of Al metal by the Al 2 Cl 7 – species , is more favorable based on Gibbs free energy. Increasing the urea concentration resulted in a clear increase in the broad peak at 74 ppm, attributed to the [AlCl 2 (urea) 2 ] + complex.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in electrolyte speciation could result in a different and/or multiple electrodeposition pathway(s), as Al-urea complexes such as [AlCl 2 (urea) 2 ] + have also been proposed to enable Al electrodeposition in addition to chloroaluminate Al 2 Cl 7 – anions. 13 , 14 Gordon et al 16 used thermochemical calculations to show that while these Al-complexed species can participate in Al electrodeposition reactions in AlCl 3 –urea mixtures, electrodeposition of Al metal by the Al 2 Cl 7 – species 16 , 33 is more favorable based on Gibbs free energy. Increasing the urea concentration resulted in a clear increase in the broad peak at 74 ppm, attributed to the [AlCl 2 (urea) 2 ] + complex.…”
Section: Resultsmentioning
confidence: 99%
“…31,[42][43][44][45][46][47][48] The formation of [Zn(AlCl 4 ) 3 ] ¹ has been clarified by Raman spectroscopy in the 67 %AlCl 3 electrolyte with ZnCl 2 . 29 Similarly, when a solid solution of Zn is dissolved in a Lewis acidic AlCl 3 -EmImCl electrolyte, the reaction in Eq. 1 is expected to proceed if the [Zn(AlCl 4 ) 3 ] ¹ complex ion is formed.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, when ZnCl 2 is added to an AlCl 3 -EmImCl ionic liquid with a 2 : 1 bath composition, [Zn(AlCl 4 ) 3 ] ¹ is formed, which is different from the Zn complexes formed in the ZnCl 2 -EmImCl ionic liquid. 29 Electrodeposition of Al-Zn alloys from [Zn(AlCl 4 ) 3 ] ¹ has been observed in AlCl 3 -EmImCl ionic liquids. 28,[30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ILs featuring bulky cations tend to result in smaller structures, opening up possibilities for various nanoscale depositions, 129 with potential applications in the fabrication of sensors. 130 Due to the ability to tune metal speciation 131 and therefore the redox potentials, ILs are found to be advantageous for deposition of various metals such as aluminum (Al) 132 and rare earth metals, 133 with impactful applications such as the fabrication of semiconductors. 134 Even though the mechanistic understanding of how the individual ions in ILs control the deposition process is not yet fully developed, 135 ILs present a significant impact on deposit morphology, attributed to their unique interfacial structuring, in some cases their specific adsorption, and ultimately their influence on the charge transfer kinetics through speciation that differ from conventional electrolytes.…”
Section: ■ Significance Of the Electrode−electrolyte Interface In Ene...mentioning
confidence: 99%